Research manual in child development - Nadelman, Lorraine (New York, N.Y. Lawrence erlbaum associates, 2004)
A hands-on lab manual in child development. It includes projects in psychomotor/perceptual, cognitive and social development. Projects are preceded by background essays on the history of that topic, related research, theoretical issues, and controversies.
Includes index.
Keywords: Child psychology -- Research -- Textbooks; Psychology -- Developmental -- Child; Psychology -- Psychotherapy -- Child & Adolescent